2016
DOI: 10.1080/0284186x.2016.1185149
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of software-assisted contour propagation from planning CT to cone beam CT in head and neck radiotherapy

Abstract: Background: Autocontouring improves workflow in computed tomography (CT)-based dose planning, but could also potentially play a role for optimal use of daily cone beam CT (CBCT) in adaptive radiotherapy. This study aims to determine the accuracy of a deformable image registration (DIR) algorithm for organs at risk (OAR) in the neck region, when applied to CBCT. Material and methods: For 30 head and neck cancer (HNC) patients 14 OARs including parotid glands, swallowing structures and spinal cord were delineate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
3
22
0
2
Order By: Relevance
“…Precision of PG propagation using DIR was evaluated by comparing these results against independent radiation oncologist CBCT re-contours (Supplementary Data H) and were found to be in excellent agreement with values reported in literature [28][29][30]. Well aligned to literature [16], the PGs included in this study demonstrated an average volume decrease of 21% and an average medial shift of 2.6 mm during HNRT.…”
Section: Discussionsupporting
confidence: 78%
“…Precision of PG propagation using DIR was evaluated by comparing these results against independent radiation oncologist CBCT re-contours (Supplementary Data H) and were found to be in excellent agreement with values reported in literature [28][29][30]. Well aligned to literature [16], the PGs included in this study demonstrated an average volume decrease of 21% and an average medial shift of 2.6 mm during HNRT.…”
Section: Discussionsupporting
confidence: 78%
“…In this study, we show the feasibility of semi‐automated contour propagation, using deformable registration of the manual contours from the prior time point. Using manually corrected semi‐automatically propagated contours is similar to our daily clinical workflow in which a radiation oncologist reviews and corrects the work of a resident, which has been reported previously …”
Section: Discussionmentioning
confidence: 99%
“…Precise immobilisation and image guided RT (IGRT) is crucial to minimise these effects. IGRT allows set-up errors to be corrected prior to treatment delivery and ensures the planned dose is consistently delivered throughout treatment [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%